2013
DOI: 10.1007/s00345-013-1127-y
|View full text |Cite
|
Sign up to set email alerts
|

Development and validation of nomograms to predict the recovery of urinary continence after radical prostatectomy: comparisons between immediate, early, and late continence

Abstract: We developed nomograms for RC at each time point after RP and validated adequately. Saving the NVB and prostate volume may affect only late RC after RP. In contrast, age, MUL, and robot-assisted surgery seem to be consistently associated with immediate, early, and late RC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
26
0
4

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(36 citation statements)
references
References 32 publications
5
26
0
4
Order By: Relevance
“…26,27 In a study by Jeong and colleagues, prostate volume was independently associated with continence at 12 months in a cohort consisting equally of RARP and RRP operated patients, although it was a predictor of 0-pad usage at 1 and 3 months following prostatectomy. 27 It has been suggested that wider dissection of the bladder neck for large prostates can contribute to this association. 28 While smaller prostate volume was associated with continence at 1 month on univariate analysis, this characteristic was not an independent predictor of continence on multivariate analysis.…”
Section: Discussionmentioning
confidence: 99%
“…26,27 In a study by Jeong and colleagues, prostate volume was independently associated with continence at 12 months in a cohort consisting equally of RARP and RRP operated patients, although it was a predictor of 0-pad usage at 1 and 3 months following prostatectomy. 27 It has been suggested that wider dissection of the bladder neck for large prostates can contribute to this association. 28 While smaller prostate volume was associated with continence at 1 month on univariate analysis, this characteristic was not an independent predictor of continence on multivariate analysis.…”
Section: Discussionmentioning
confidence: 99%
“…A total of 1738 patients (780 RRP, 937 RARP, and 21 laparoscopies [LP]) were included in the four studies reporting the hazard ratio for the recovery of continence [20,22,24,26]. For the study reporting the OR of a return to continence at 1 mo, a total of 872 patients (416 RRP and 456 RARP) were included [18], for the studies at 3 mo 2517 patients (571 RRP, 1697 RARP, and 249 LP) were included [14,19,21,22,25,26], at 6 mo 3187 patients (1667 RRP, 589 RARP, and 931 LP) were included [14,16,26], and at 12 mo 4656 patients (2555 RRP, 998 RARP, and 1103 LP) were included [1518,23,26]. …”
Section: Evidence Synthesismentioning
confidence: 99%
“…The use of an endorectal coil was used in four studies [16,21,24,26], not used in four studies [14,22,23,25], and not reported in five studies [15,1720]. MUL was measured in either: (1) the coronal plane in six studies [16,1921,25,26], (2) the sagittal plane in three studies [14,17,22], (3) the sagittal plane cross-referenced with the coronal plane in two studies [23,24], and (4) not reported in two studies [15,18]. …”
Section: Evidence Synthesismentioning
confidence: 99%
See 1 more Smart Citation
“…'ları kontinans açısından nomogram geliş-tirmek için yaptıkları bir çalışmada, RYLP ile ARP vakaları randomize edilerek karşılaştırmışlardır. Multivarite analizinde RYLP, genç yaş ve membranoz uretra'nın uzunluğu 1., 3. ve 12. ay kontinans iyileşmesi açısından anlamlı öngörücüler olarak bulunurken; prostat boyutu ve sinir koruyucu yaklaşım sadece 12. ay kontinans iyileşmesinde anlamlı öngörücü olarak bulunmuştur (46).…”
Section: Posterior Ve Anterior Rekonstrüksiyonunclassified